Fatigue characteristics of deep excavation-disturbed jinping marble - Anlin Zhang; Ru Zhang; Ting Ai; Li Ren; Zetian Zhang; Jing Xie; Chendi Lou; Kun Xiao; Zeqian Yang (Journal of Rock Mechanics and Geotechnical Engineering)
Deep rocks encountered in underground engineering are frequently in complex in situ environments and experience both excavation disturbance during construction and cyclic loading throughout the long-term operation. Understanding the fatigue behavior of excavation-disturbed rocks in complex stress environments is critical for assessing the long-term stability of deep rock structures. Hence, an experimental method has been developed to capture the fatigue damage process of rocks while considering the in situ environment and excavation disturbance. Using this method, a series of triaxial fatigue damage experiments were conducted on Jinping deep marble samples from various in situ environments of 100 m, 1000 m, 1800 m, and 2400 m to better understand the variation in fatigue characteristics at different depths. With increasing depth, the samples experienced more cycles and greater fatigue deformation before failure. Further insights were gained into the fatigue damage behavior in terms of stiffness degradation, energy dissipation and irreversible strain accumulation. A decrease in the elastic modulus and an increase in the dissipated energy and irreversible strain exhibit an evolution pattern of initial→stabilization→acceleration, reflecting the nonlinear fatigue process that occurs inside marble. With increasing depth, marble samples have longer fatigue lives but exhibit more significant stiffness loss, energy dissipation and irrecoverable deformation accumulation; thus, evaluating the instability of deep rock structures solely using fatigue life alone is inadequate. Moreover, the previously reported inverted S-shaped evolution of fatigue damage was observed, and it was found that an increase in depth leads to an earlier onset of the accelerated fatigue damage stage with greater dominance of fatigue failure. Based on the nonlinear strain, loading cycle variable and fatigue life, a highly accurate nonlinear fatigue model was developed to describe the complete inverted S-shaped evolution pattern of fatigue damage, which demonstrated excellent practical implications for the theoretical characterization of anisotropic fatigue damage in disturbed Jinping marble.